2020
DOI: 10.1111/dth.14364
|View full text |Cite
|
Sign up to set email alerts
|

Cause and management of lipedema‐associated pain

Abstract: Lipedema is a painful, underdiagnosed adipose tissue disorder, characterized by symmetrical swelling of the extremities due to subcutaneous fat deposition in the buttocks, thighs, legs, and arms, sparing the most distal part of the extremities. Although etiology and pathogenesis of lipedema is unclear, possible role of hormonal and genetic factors have been proposed previously. Patients with lipedema suffer from pain, easy bruising, tenderness, and disfigurement. Pain is the leading symptom in lipedema. Since … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
1
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 37 publications
0
43
1
7
Order By: Relevance
“…In the studies selected by the authors, a relationship was observed between mental disorders and the level of perceived pain in patients with lipoedema. Stigmatization, labelling, and downplaying of suffering affects lipoedema patients’ mental states, which makes it difficult to implement effective therapy and increases the level of experienced pain [ 20 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the studies selected by the authors, a relationship was observed between mental disorders and the level of perceived pain in patients with lipoedema. Stigmatization, labelling, and downplaying of suffering affects lipoedema patients’ mental states, which makes it difficult to implement effective therapy and increases the level of experienced pain [ 20 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the relationship with SNs, recent studies have revealed that adipose tissue modulates systemic metabolism through secretion of endocrine and paracrine factors such as leptin and TNFα from adipocytes, immune cells and endothelial cells within adipose tissue to local SN fibers to transmit these adipose signals to CNS, which subsequently initiates output to other tissues [115] . Clinical observations that patients with lipedema suffer from pain and that liposuction significantly reduces pain [116] suggest that adipocytes may secrete noxious signals to SNs to evoke pain such as CABP. SN fibers in turn release neurotransmitters such as CGRP and SP to regulate the differentiation and function of adipocytes.…”
Section: Interactions Of Nerves With Cellular Components Of Bone Metastasismentioning
confidence: 99%
“…Prolonged standing or sitting (as at the end of the day) can also cause discomfort. [3] Exercise or warm weather can precipitate pain. [17] e defining feature of lipedema is a disproportionate distribution of body fat on hips, buttocks, thighs, and lower legs, in a gynoid pattern, producing a disproportion between the upper and lower halves of body.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…[17] e defining feature of lipedema is a disproportionate distribution of body fat on hips, buttocks, thighs, and lower legs, in a gynoid pattern, producing a disproportion between the upper and lower halves of body. [3] Hands and feet are typically spared. e appearance is also known as the "saddle bag phenomenon, " because it mostly affects the hips and thighs while the rest of the body maintains normal proportions.…”
Section: Clinical Featuresmentioning
confidence: 99%
See 1 more Smart Citation